From Essentialism to Worldview: - M. Endy Saputro (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2016)
This paper aims to understand formation of indigenous knowledge production in Center for Religious and Cross-Cultural Studies (CRCS), Graduate School, Gadjah Mada University. One main question analyzed here is mainly focused on definitions of indigenous religions embraced by CRCS students. Consequently, CRCS students’ theses submitted in the CRCS library from 2003 until 2012 would be employed as the representative subject to look at the discourse of indigenous definition offered by the students. There are 29 of 192 theses located as the representative subject. I argue that there is a shifting paradigm of indigenous religion in CRCS from essentialism paradigm to worldview one. Keywords: Indigenous, Religion, Culture